Analisis Pengaruh Harga, Produk, Perilaku Konsumen Terhadap Keputusan Pembelian Telon Lang - Bida Sari; Estu Mahanani (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia (BPJP - STIE), 2017)
This study aims to determine the effect of variable price (X1), product (X2) and consumer behavior (X3) on buying decisions (Y). The method used is the interactive-associative research. This research population is all of the people who live at RT.13 and RT.14 RW.07 North Utan Kayu, East Jakarta.The sampling technique is done by Accidented Sampling of 67 respondents who attendCSR event “Kunjungan Posyandu Telon Cap Lang” PT. Eagle Indo Pharma at Posyandu RW.07.Data collection is using observation, interviews and questionnaires. Analysis of the data used is quantitative analysis, including correlation analysis, determination analysis and multiple linear regression analysis (simultaneously), and hypothesis testing using t-test and F-test.The results of data processing performed with SPSS 19.0 forwindows. The value of correlation coefficient (R) is 0.950.The value of determination coefficient is(R2) = 0.903. It means that 90.3%variation of dependent variable (decision of buying) could be predicted from the combination of variables (pricing, product and consumer behavior)and the remaining 9.7% is influenced by other factors. The regression equation was obtained Y = 1,291+ 0.289 X1 + 0.476 X2 + 0.205 X3. For the F test obtained F value is calculated at 142.689, greater than F-table (2.807) with α = 5%, so the conclusion: reject Ho and Ha is accepted. It means there is significant influence of variable price (X1), product (X2) and consumer behavior (X3) together on decision of buying(Y).